2001
DOI: 10.1002/humu.1192
|View full text |Cite
|
Sign up to set email alerts
|

Congenital insensitivity to pain with anhidrosis (CIPA): Novel mutations of theTRKA (NTRK1) gene, a putative uniparental disomy, and a linkage of the mutantTRKA andPKLR genes in a family with CIPA and pyruvate kinase deficiency

Abstract: Congenital insensitivity to pain with anhidrosis is an autosomal recessive hereditary disorder characterized by recurrent episodic fever, anhidrosis (inability to sweat), absence of reaction to noxious stimuli, self-mutilating behavior, and mental retardation. The human TRKA gene (NTRK1), located on chromosome 1q21-q22 encodes the receptor tyrosine kinase for nerve growth factor. We reported that TRKA is the gene responsible for CIPA and we developed a comprehensive strategy to screen for TRKA mutations and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…The NTKR1 gene encodes the neurotrophic tyrosine kinase-1 receptor and belongs to a family of nerve growth factor receptors whose ligands include neurotrophins. Mutations in the NTKR1 gene have been associated with a rare congenital insensitivity to (Indo et al, 2001). Much more common is intrachromosomal rearrangement or translocation of the NTKR1 gene in papillary thyroid carcinoma (Brzeziań ska et al, 2007) arising from the fusion of the 3 0 terminal sequences of the NTRK1 with 5 0 terminal sequences of Figure 4.…”
Section: Discussionmentioning
confidence: 97%
“…The NTKR1 gene encodes the neurotrophic tyrosine kinase-1 receptor and belongs to a family of nerve growth factor receptors whose ligands include neurotrophins. Mutations in the NTKR1 gene have been associated with a rare congenital insensitivity to (Indo et al, 2001). Much more common is intrachromosomal rearrangement or translocation of the NTKR1 gene in papillary thyroid carcinoma (Brzeziań ska et al, 2007) arising from the fusion of the 3 0 terminal sequences of the NTRK1 with 5 0 terminal sequences of Figure 4.…”
Section: Discussionmentioning
confidence: 97%
“…6 In addition, there are several reports of children with CIPA who bit off a portion of their tongue or pulled out their own teeth. [15][16][17] Health care maintenance issues are important for children with CIPA: Rosemberg et al 18 reported that an estimated 20% die from hyperpyrexia in the first 3 years of life, while Shorer et al 12 report sepsis leading to death in 23% of their CIPA patients. However, other groups have not reported similar mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal UPD has been reported in Herlitz junctional epidermolysis bullosa [Pulkkinen et al, 1997;Takizawa et al, 1998], insulin-dependent diabetes mellitus [Field et al, 1998], developmental delay [Rothlisberger et al, 2001], and ChediakHigashi syndrome [Dufourcq-Lagelouse et al, 1999]. Paternal UPD has been described in pycnodysostosis [Gelb et al, 1998], Herlitz junctional epidermolysis bullosa [Takizawa et al, 1998[Takizawa et al, , 2000, retinitis pigmentosa [Rivolta et al, 2002], retinal dystrophy [Thompson et al, 2002] and congenital insensitivity to pain with anhidrosis [Miura et al, 2000;Indo et al, 2001]. UPD can be complete isodisomy [Dufourcq-Lagelouse et al, 1999;Miura et al, 2000], or partial isodisomy [Rivolta et al, 2002], with or without heterodisomy.…”
Section: Resultsmentioning
confidence: 97%